In Vitro Effects of the Acylated StreptokinasePlasminogen Activator Complex BRL 33 575 Incubated with Normal Human Plasma - Lämmle, B; Noll, G; Tran, T H; Lohri, A; Duckert, F (Thrombosis and Haemostasis, 1984)
Thrombolysis with acylated streptokinase-plasminogen complexes is aimed to achieve fibrinolysis without systemic fibrinogenolysis. The p-aminobenzoyl-streptokinase-(Lys)-plasminogen-complex (BRL 33 575) should be particularly useful due to its slow deacylation rate. Unexpectedly, repeated doses of 10 mg of BRL 33 575 (corresponding to 310'000 streptokinase equivalent units) induced systemic effects in patients though less than streptokinase alone. In vitro incubation of normal human plasma with BRL 33 575 at concentrations used in patients resulted in nearly complete consumption of α2-antiplasmin and plasminogen and significant fibrinogenolysis within 3 hr. This demonstrates that - despite of slow deacylation of BRL 33 575 - the small amounts of activator generated are highly efficacious in activating plasma plasminogen under conditions in which no physiological clearance of the free activator takes place. Simulating the calculated activator release from BRL 33 575 by infusing equivalent amounts of streptokinase into plasma resulted in less pronounced effects. This is probably explained by anti-streptokinase antibodies which will neutralize the initially infused streptokinase but will be bound by BRL 33 575.Our in vitro experiments indicate that further clinical studies should be done with lower doses of BRL 33 575 or prolonged dosage intervals.
Keywords: Thrombolysis; Acylated streptokinase-plasminogen complex; α2-antiplasmin; Plasminogen; Fibrinogen